INFLUENCE OF PERMANGANATE INDEX IN THE PARAMETERS AS TOTAL PHENOL CONTENT AND TOTAL ANTIOXIDANT ACTIVITY OF EXTRACTS OF CAMELLIA SINENSIS - Mello, Lucilene Dornelles; Tunes, Tiele Garcia (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: This study estimated the Permangante Index (IKMnO4) and evaluated its correlation with parameters as total phenols (FT) and total antioxidant activity (TAA) of commercial teas of Camellia sinensis, fermented, unfermented and blended with other plants. Methods: The aqueous extracts were prepared from commercial samples of green and black teas, green tea blended with lemon (Camellia sinensis with Citrus limonium), green tea blended with mint (Camellia sinensis with Mentha piperita), green tea blended with peach (Camellia sinensis with Prunus persica) and green tea blended with orange (Camellia sinensis with Citrus sinensis). The Permangante index was determined by titrating the tea extract with potassium permanganate solution according to AOAC method (AOAC, 1980) with modifications. The concentration of phenols in the extracts was determined by spectrophotometry according to the standard procedure of Folin-Ciocalteau. The antioxidant activity of the extracts was evaluated using the radical 1,1-diphenyl-2-picrylhydrazyl (DPPH—) method. All the determinations were performed in triplicate, and the results presented as mean ± standard deviation (SD). The data were evaluated by univariate statistical analysis (ANOVA), F-test and mean test (Tukey´s test) for comparative results. Pearson's correlation was used to measure the degree of linear correlation and the quantitative variables were from a normal population. Results: The results for Permanganate Index show a variation ranged from 0.40 to 0.80 mEq/l. The ANOVA analysis to IKMnO4 shown there is significant statistically difference at the 5% probability level (p < 0.05) between the types of tea as well as the amount of herb used to prepare the infusion. Therefore, it was observed that there significant contrast between tea extracts, the mixture of different plants in blended extracts as well as the tea manufacture process affect the polyphenols tannins content influencing the permanganate index parameter. Studies correlation shown strong correlations (r > 0.7) among the parameters. For the Camellia sinensis extracts the high correlations between IKMnO4 and TAA; FT and TAA demonstrates the suitability of the permanganate index in the evaluation of antioxidant activity. Conclusion: The results suggest that the Permanganate Index could be used for quality control of tea as an additional parameter.